Going Nowhere in a Hurry? The Pacific’s EPA Negotiations with the European Union - Kelsey, Jane (Victoria University of Wellington Law Review, 2007)
This paper explores the Economic Partnership Agreement (EPA) negotiation process of the EU-ACP with a focus on the Pacific region. To comply with the requirements of the Cotonou Agreement 2000 and the requirements of the WTO EPAs must be negotiated before 2008. They will replace the trade arrangements between the EU and the ACP States pursuant to the Cotonou Agreement 2000. The Pacific states have proposed a creative EPA text to address their concerns about the effects of any new agreement with the EU. Professor Kelsey’s view is that the Pacific ’wish list’ contains two intrinsic tensions : one between its trade liberalisation and development agendas, and the other between the affirmation of sovereign integrity and supranational institutional arrangements. Moreover, the EU and the Pacific states have different trade interests and the demands made by the Pacific states have largely been rejected by the EU. The conclusion is that the production of a final text of the Pacific EPA is not imminent. This paper was written prior to the military coup in Fiji on 5 December 2006 and does not discuss the significant implications of that event for the negotiations.